Study of the treatability of wastewater from a coal-gasification plant. Final report, July 15, 1978-July 14, 1980 - Iglar, A. F. (East Tennessee State Univ., Johnson City (USA). Dept. of Environmental Health, 1980)
This study focused on the coal gasification facility serving the Holston Army Ammunition Plant in Kingsport, Tennessee. Objectives were to characterize the wastewater produced by the gasification facility, and to evaluate technology for treating the waste in preparation for dischage to the environment. Most wastewater was recycled for scrubbing and cooling the product gas, with the excess requiring disposal found to be an average of only 1170 gallons per day (53 gallons per ton of coal, as received, and 366 gallons per million cubic feet of product gas). Analysis indicated that the waste was warm, high in alkaline material, especially ammonia, high in organic material, especially phenols, and also contaminated with other substances. Sulfides and thiocyanates were especially high in concentration. It was found that pretreatment could be accomplished by stripping (air injection) at high pH, removal of grease and oil (by pH suppression and light aeration) and neutralizatin. Equations were developed to describe the first two steps. Biological treatment through activated sludge was found to be successful, but effected only a moderate degree of treatment, and was troubled with frequent process upset. Attempts to improve treatment efficiency and stability are described. The data indicated the need to study aerated waste stabilization ponds as an alternative to activated sludge. Biological reaction kinetics were studied for activated sludge. Evaluation of the application of granular activated carbon suggested that this could be an effective practical tertiary treatment.